Decision-feedback differential detection based on linear prediction for 16DAPSK signals transmitted over flat Ricean fading channels. - Schober, R.
In this article, prediction-based decision-feedback differential detection (DF-DD) for 16-level differentially encoded amplitude/phase-shift keying is proposed. Unlike previously reported DF-DD schemes, this scheme provides a performance gain over conventional differential detection under general Ricean fading conditions. A further important advantage of the novel scheme is that it is able to compensate a small carrier frequency offset. The linear predictor coefficients may be updated using the recursive least-squares algorithm, which can start blind, i.e., without a priori knowledge about the channel statistics and without a training sequence. This makes the scheme attractive for application in mobile communications since the statistics of a nonstationary mobile channel can be tracked
Keywords: 16DAPSK signals; Blind starting algorithm; Carrier frequency offset compensation; Differentially encoded amplitude/phase-shift keying; Flat Ricean fading channels; Linear predictor coefficients; Mobile communications; Nonstationary mobile channel statistics; Performance gain; Prediction-based decision-feedback differential detection; Recursive least-squares algorithm